The use of bone autoplasty for false joints of the humerus diaphysis - K. I. Khorak; P. G. Kogan; D. G. Parfeev; A. I. Avdeev; A. M. Morozov; M. E. Piskareva (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2024)
Relevance. Fractures of the diaphysis of the humerus account for 1–5% of the total number of traumatic skeletal injuries and 20% of the number of humerus injuries. At the same time, in modern society there is no tendency to reduce traumatism, therefore, the number of surgical interventions aimed at restoring the integrity of the bone does not decrease. Over the decades, approaches to tactics and choice of drugs for correction of defects for fusion and restoration of motor function of the limb have been changing. Physicians from different countries have tried to use both auto- and allografts, with the results they achieved significantly increasing the chances of survival of the transplanted material. The multitude of studies conducted in different countries only confirms their high relevance, which makes the task of pseudarthrosis treatment one of the most important, but at the same time one of the most difficult in traumatology and orthopedics injuries.Objective. To study the application of bone autotransplantation for the treatment of false joints of the diaphysis of the humerus diaphysis.Materials and methods. A review of the literature sources published in the last 5 years on the problem of application of bone autografting methods for false joints of the humerus diaphysis was carried out.Results. Disruption of the process of humerus fusion and formation of a false joint make surgical intervention inevitable, and the results of treatment directly depend on the determination of the correct indications for a certain type of surgical intervention and competent implementation of the treatment plan. The chosen treatment tactics allow successful restoration of the anatomy and function of the damaged segment. There are many different methods of surgical treatment of false joints. The main purpose of bone-plastic materials application in traumatology and orthopedics is optimization of reparative osteogenesis.Conclusion. Over the last decades, clinical practice has changed many approaches to the tactics and choice of therapeutic means to restore bone integrity, as well as to restore the supporting and motor functions of the traumatized limb. Analysis of the data obtained from the literature has shown that the best results in the treatment of false joints of the humerus diaphysis were demonstrated by the techniques combining the use of bone autoplasty and additional metal structures.